An update on the various practical applications of the STOP-Bang questionnaire in anesthesia, surgery, and perioperative medicine. Issue 1 (February 2017) - Nagappa, Mahesh; Wong, Jean; Singh, Mandeep; Wong, David T.; Chung, Frances
Abstract : Purpose of review: The present review aims to provide an update on the various practical applications of the STOP-Bang questionnaire in anesthesia, surgery, and perioperative medicine. Recent findings: The STOP-Bang questionnaire was originally validated as a screening tool to identify surgical patients who are at high-risk of obstructive sleep apnea (OSA). A recent meta-analysis confirmed that STOP-Bang is validated for use in the sleep clinic, surgical, and general population. Patients with a STOP-Bang score of 0–2 can be classified as low-risk for moderate-to-severe OSA. Those with a score of 5–8 can be classified as high-risk for moderate-to-severe OSA. In patients with a score of 3 or 4, a specific combination of a STOP score at least 2 + BMI more than 35 kg/m 2 or STOP score at least 2 + male or STOP score at least 2 + neck circumference more than 40 cm indicates higher risk for moderate-to-severe OSA. Further, patients with a STOP-Bang score at least 3 can be classified as high risk for moderate-to-severe OSA if the serum HCO3 - at least 28 mmol/l. STOP-Bang can be used as a novel tool for perioperative risk stratification because it easily identifies patients who are at increased risk of perioperative complications. Summary: STOP-Bang at least 3 was recommended previously to identify the suspected or undiagnosed OSA. To reduce the false positive cases and to improve its specificity, a stepwise stratification is recommended to identify the patients at high risk of moderate-to-severe OSA. Because of its practical application, STOP-Bang is a useful screening tool for patients with suspected or undiagnosed OSA.